Mechanism of coping in patients of alcohol dependence and its correlation with anxiety, depressive symptoms - Bharati, Anup S.; Matcheswalla, Y. A.; Umate, Maithili S.; Jaiswal, Suyog (International Journal of Advances in Medicine, 2017)
Background: Alcohol use disorder is a common and challenging problem in India. In various studies the prevalence of co-morbid psychopathologies ranges from 15-70% including depression & anxiety disorders. Coping mechanisms of individual play vital role in case of developing alcohol dependence and various psychopathologies. A complex interaction of psychopathologies, coping skills, and alcohol use can influence the outcome of alcohol dependence. This study was undertaken with the aim of studying coping mechanism along with anxiety, depressive symptoms and their correlation in patients of alcohol dependence. Methods: This was a cross sectional study conducted in a tertiary government hospital. Institutional ethics committee approval obtained. 152 patients with the diagnosis of alcohol dependence (DSM IV TR) were screened for inclusion and exclusion criteria, out of which 60 patients were enrolled after taking written informed consent. Following scales were used for the study, mechanisms of coping scale (MOCS), Hamilton anxiety rating scale (HAM-A), Montgomery-Asberg depression rating scale (MADRS). Results: 32 patients had HAM-A score >17 suggestive of anxiety, similarly 40 patients had MADRS score >7 indicating depression. Problem focussed coping mechanism such as problem solving is associated with better outcome in terms of lesser anxiety and later age of first drink as well as developing dependence. Passivity, which is an emotion focussed coping mechanism, is associated with earlier first drink and higher depression score in patient suggesting poor outcome. Conclusions: Coping skills training should be incorporated in abstinence focused programs. Co-morbid psychopathologies like anxiety and depression are common in alcohol dependence individuals and thus, screening for these symptoms is essential for early interventions and better outcomes.